The functions of the legal model of the real state circulation system - V. A. Petrushkin (Russian Journal of Economics and Law)
Objective: to analyze the concept of legal modeling in the field of real estate circulation as a method of scientific research. Methods: abstract logic and method of comparative analysis. Results: The principles are proposed for the functioning of the legal system model of the real estate circulation; the author reveals approaches to the definition of "real estate object". Scientific novelty: The research of the content of the "real estate object" notion resulted in the classification of the legal model of the real estate circulation system; revealed the structure of the circulation mechanism, including legal procedure. Practical value: The approaches were developed to define the individual elements of the legal model of real estate circulation system; the conclusion is made that the concept of "legal model" differs from the related categories. Such a notion, in all cases, has the function of legal modeling and is instrumental in nature.